2018
DOI: 10.1186/s40168-018-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet during pregnancy is related with the infant stool microbiome in a delivery mode-dependent manner

Abstract: BackgroundThe gut microbiome has an important role in infant health and immune development and may be affected by early-life exposures. Maternal diet may influence the infant gut microbiome through vertical transfer of maternal microbes to infants during vaginal delivery and breastfeeding. We aimed to examine the association of maternal diet during pregnancy with the infant gut microbiome 6 weeks post-delivery in mother-infant dyads enrolled in the New Hampshire Birth Cohort Study. Infant stool samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 47 publications
9
142
2
2
Order By: Relevance
“…Interestingly, an infant's GM may also be determined by maternal gestational diet through a vertical transfer of maternal microbes to infants during vaginal delivery and breastfeeding. This theory is confirmed by the study of Lundgren et al [34], who identified distinctions in infant microbial community structure dependent on maternal fruit and milk intake during pregnancy, but this effect differs according to the delivery model. Additionally, reports are suggesting that transmission of commensal bacteria from mother to fetus is likely to occur prior to parturition [35].…”
Section: Introductionsupporting
confidence: 52%
“…Interestingly, an infant's GM may also be determined by maternal gestational diet through a vertical transfer of maternal microbes to infants during vaginal delivery and breastfeeding. This theory is confirmed by the study of Lundgren et al [34], who identified distinctions in infant microbial community structure dependent on maternal fruit and milk intake during pregnancy, but this effect differs according to the delivery model. Additionally, reports are suggesting that transmission of commensal bacteria from mother to fetus is likely to occur prior to parturition [35].…”
Section: Introductionsupporting
confidence: 52%
“…First, although maternal ethnicity/race, age, education, marital status, time of sampling, and mode of delivery were included as potential confounders in the model, our sample size restricted the ability to consider a broader range of covariates. Second, this study lacks information on dietary intakes, while recently several studies show the important role of diet in shaping gut microbiome (Gohir et al, ; Lundgren et al, ; Makki, Deehan, Walter, & Bäckhed, ). Third, this study lacks biological markers of HPA‐axis functioning such as cortisol levels, which are known to correlate with stressful life events and psychopathology (Rubinow, Post, Savard, & Gold, ).…”
Section: Discussionmentioning
confidence: 94%
“…The intestine contains a large number of microorganisms, which play an important role in human and animal health. Host genetics and external factors such as delivery mode [41,42], environment [9], nursing milk [43], and solid feed [13] have been reported to contribute to the development of the gut microbiota of infants. Compared with adult intestinal micro ora, the neonatal intestinal micro ora is truly a dynamic state.…”
Section: Effect Of Es On Jejunum Microbiome and Metabolome Of Bamei Smentioning
confidence: 99%